Avaliação da predação, aspectos de nidificação e percepção ambiental em podocnemis expansa (schweigger, 1812) e podocnemis unifilis (troschel, 1848) (testudines, podocnemididae) em rios das bacias Araguaia/TO, Xingu e Teles Pires/MT - Tosta, Carla Salim (Universidade Federal do Tocantins, 2019)
The present study aimed to evaluate the aspects that are involved in the nesting and the predation of nests and individuals of Podocnemis expansa and Podocnemis unifilis, as well as to understand the environmental perception of students of a public school in Lagoa da Confusão - TO on both species mentioned. At the beaches, data were collected on the predation of nests and individuals, and on environmental variables (soil compaction, beach elevation and total beach area). Among the factors that may influence the choice of spawning site, we obtained significant results in the beach height variable for P. expansa and in soil compaction for P. unifilis. The predation of individuals, whether natural or anthropic, is great for both species, since species are appreciated for human consumption in many of the localities that occur, however, it seems to be more expressive for P. unifilis (75.7%), whose nests are shallower, and therefore more vulnerable to predators, some sampled beaches have higher rates of predation than others. P. expansa has it less in its adulthood, because its size hampers predators, still, anthropic predation is present at all ages for these animals, which have an annual life cycle and slow population growth. The environmental perception of the students revealed a lack of general knowledge about the species of this study, as well as ecological aspects, which is worrying, since the species are consumed, mainly by the riverside population. Further studies are needed to deeply understand the aspects that may influence the nest choice behavior, and such information may be valuable for the conservation of these chelonians. Investing in projects that involve the community in the management and protection of these animals is also necessary to avoid their population decline.